Influence of Fruit Ripening Stage, Post-Harvest Seed Development, and Genotypic Variation on the Mass of 1000 Seeds in Eggplant - Popović, Vukašin; Vlajić, Slobodan; Takač, Adam (Journal of Agricultural Sciences (Belgrade), 2026)
This study examined the effects of fruit ripening stage and post-harvest seed development on the mass of 1000 seeds in eggplant (Solanum melongena L.) across three morphologically distinct varieties (Serbian, Chinese, and Italian). Field experiments were conducted over three years (2017–2019) at the Institute of Field and Vegetable Crops in Novi Sad, Serbia. Fruits were harvested at unripe, semi-ripe, and fully ripe stages, then stored for 10 or 20 days at 20–25°C prior to seed extraction. Seeds were obtained following a three-day fermentation process and evaluated according to ISTA Rules. Fruit ripening stage was the predominant factor, explaining over 97% of the variation in seed mass. Seeds from fully ripe fruits consistently exhibited the highest mass, up to 68% greater than those from unripe fruits. Post-harvest storage increased seed mass across all ripening stages, indicating continued seed filling after harvest. Seeds extracted after 20 days showed significantly higher mass than those extracted after 10 days. The Serbian variety achieved the highest mass of 1000 seeds at full ripeness, while the Italian variety reached peak values at the semi-ripe stage following both storage durations. In contrast, the Chinese variety consistently exhibited the lowest values, highlighting genotypic differences in seed development potential. These results confirm that fruit physiological ripening and post-harvest storage significantly influence seed quality. Delaying seed extraction is an effective strategy to enhance the mass of 1000 and seed vigor, offering practical implications for breeding and seed production.